(untitled) (Journal of Forest and Livelihood, 2019)
Conservation of Chure landscape is at the limelight of public policy debate given its geo-ecological and socio-economic prominence and its real and perceived environmental degradation. The dominant narrative of the Chure environmental crisis coupled with increasing pressures of some political constituencies prompted government’s declaration of the Chure as Environmental Protected Area. This policy response of the state has engendered contestations and dissonance among different actors associated with the Chure. This paper is based on review of relevant literature, direct observation and participation in the national and regional policy dialogues and public debate. We identify two broad strands of contested actors: the ones who strongly favor the government policy decision and those who are opposing it. We argue that this can be attributed to the competing understandings of the problem and the proposed solutions to the Chure conservation. Actors’ understandings of the Chure are based on their own identical political strands and do not necessarily reflect the underlying causes at the ground. The politics of scientific facts and evidences is also critical to this contestation. We identified three major strands of management approaches in the Chure discourse: state centric, community based and state-community collaborative. Deliberative scrutiny of current policies and attention to the political ecology of conservation could help arrive at negotiated understanding of the problem and sustainable approach to the Chure management.